Contributing to social transformation through occupation: Experiences from a think tank. Issue 2 (3rd April 2019) - Laliberte Rudman, Deborah; Pollard, Nick; Craig, Claire; Kantartzis, Sarah; Piškur, Barbara; Algado Simó, Salvador; van Bruggen, Hanneke; Schiller, Sandra
ABSTRACT: Occupational therapy is underpinned by the premise that engagement in occupation is fundamental to health and well-being. Through occupations, people are able to orchestrate their lives in ways that enable them not only to survive, but also to experience human flourishing. Through occupation, people can develop and maintain their families, neighbourhoods and communities as sources of belonging, opportunities and common action. Occupation, therefore, is not only important to each individual, but also, through collective occupation, people develop the kind of lives that they live together. Occupation is an essential factor in life quality, the experience of being human and the social transformation of individuals and of the societies of which people are a part. This article describes the formation of an International Think Tank for Occupation based social transformation. It begins with a brief overview of the conditions and context that underpinned the development of the group, and the milestones achieved to date in the establishment of a global network.